PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, KONFLIK ANTAR PERAN, DAN MOTIVASI TERHADAP KEINGINAN BERPINDAH KERJA AUDITOR DARI KANTOR AKUNTAN PUBLIK DI SEMARANG - Choirun Nisa, 08.3503.0508 Aniswatin; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2012)
This study aimed to analyze the effect of job satisfaction, organizational commitment, role conflict and motivation to move desires auditors working on a public accounting firm in Semarang. The population in this study are all auditors in public accounting firm. Sample size is 48 data. The research sample collected by direct interviews or in interviews in respondents with a minimum criteria has been working in public accounting firm for one year.The method used in this research is to use multiple regression analysis results indicate that job satisfaction, commitment Oganisasional, and negative and significant motivation to move kerja.Sedangkan keiinginan berpengaruh role conflict between positive and significant impact on the desire to move the work auditor. Saran Researchers further to add variable consequences in order to know the cause of the desire to move the work factor Auditor.Keywords: job satisfaction, organizational commitment, role conflict, motivation, desire to move work